Membrane life estimation in full-scale immersed membrane bioreactors - Ayala, D. F.; Ferre, V.; Judd, Simon J. (Elsevier Science B.V., Amsterdam., 2011)
Limited quantitative available information exists regarding the robustness of membranes used in immersed membrane bioreactor (iMBR) applications, and no information on the relative contribution of the two main membrane failure modes of permeability and integrity loss. Such information is crucial given the significance of membrane replacement costs to the viability and sustainability of iMBRs. Measurements of membrane permeability and integrity have been made on flat sheet (FS) membrane cartridges sampled from six existing full-scale iMBRs. The recovered membrane permeability (i.e. the permeability recorded following chemical cleaning) revealed all plants operating for less than six years to have a clean water flux greater than that of the virgin membrane cartridge. A lower permeability was recorded only for the oldest plant (eight years of operation), and this was attributed to high levels of phosphate scale fouling. Assigning a linear trend between membrane permeability loss and operation time indicated the recovered membrane permeability to reach a threshold minimum value for virgin membrane cartridge after ∼7 years of operation. The membrane cartridge integrity, as measured by the strength of the weld at its perimeter, correlated with the total volume of water permeated per cartridge, the total weight of NaOCl cleaning reagent to which the panel has been exposed, and the mean volume of water permeated per cartridge between chemical cleans. In this case, the linear trend indicated a membrane life equating to ∼900m3 per panel or exposure to a total of 1.3kg NaOCl before the threshold minimum welding strength for membrane cartridge was reached. As with the permeability data, only for the oldest plant was the measured mean membrane integrity below the threshold. The data indicate membrane life for FS iMBRs to exceed six years, on the basis of both permeability and integrity, and may ultimately be limited only by the irreversible deposition of inorganic scale, rather than operation t
Keywords: Flat sheet membrane; Membrane bioreactor; Integrity; Membrane life; Inorganic scaling